2011
DOI: 10.1108/09556221111136476
|View full text |Cite
|
Sign up to set email alerts
|

Effects of process parameters on mechanical properties of coated fabrics

Abstract: PurposeThe purpose of this paper is to examine the effects of coating process parameters (base fabric, coating material, coating technique and production parameters) on mechanical properties of coated fabrics.Design/methodology/approachIn this research, 24 coated fabrics were produced under controlled production conditions by using two cotton base fabrics and two coating materials as polyurethane (PU), PU/silicone in order to study how coating affects some of the base fabric's mechanical properties such as bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 9 publications
(5 reference statements)
0
25
0
Order By: Relevance
“…The consideration of Figure 3 indicates that, after application of polymers, the elongation at break and tensile strength were decreased moderately, compared to the reference sample, i.e., elongation at break by 3–11% (warp) and 0.04–16% (weft), and tensile strength by 3–18% (warp) and 7–22% (weft). This could be explained by the fact that the coating penetrates the fabric sample and inhibits the mobility of the yarns in the fabric structure, causing the fabric to become more rigid and inflexible [ 21 , 22 ]. The fabric rigidity depends also on the characteristics of the polymers used, the application conditions, and undesired linkages between the coated fibres, so-called bridges.…”
Section: Resultsmentioning
confidence: 99%
“…The consideration of Figure 3 indicates that, after application of polymers, the elongation at break and tensile strength were decreased moderately, compared to the reference sample, i.e., elongation at break by 3–11% (warp) and 0.04–16% (weft), and tensile strength by 3–18% (warp) and 7–22% (weft). This could be explained by the fact that the coating penetrates the fabric sample and inhibits the mobility of the yarns in the fabric structure, causing the fabric to become more rigid and inflexible [ 21 , 22 ]. The fabric rigidity depends also on the characteristics of the polymers used, the application conditions, and undesired linkages between the coated fibres, so-called bridges.…”
Section: Resultsmentioning
confidence: 99%
“…The application of conductive polymer enlarged elongation at break and breaking tenacity of Co slightly, i.e., from 8.84 up to 9.58 (warp), from 14.64 up to 15.63 (weft), and from 477 up to 495 (warp), from 388 up to 400 (weft), respectively, and, on the other hand, reduced elongation at break of PES significantly, as well as enlarging tensile strength and breaking tenacity of PES drastically. Printing paste penetrates the fabric structure and prevents the yarns’ mobility, causing fabric’s rigidity and inflexibility [ 19 ], which is also connected with the composition of the paste, the type of fibres, and undesired linkages between treated fibres [ 4 ]. The admixture of binder into conductive paste influenced the mechanical properties of PES more negatively than Co.…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with previous results (Åkerfeldt et al 2013b) where it was concluded that increased amounts of binder polymers increased the brittleness of a PET substrate, making the yarns more brittle, whereas increased PEDOT:PSS and EG amounts led to increased ductility, with respect to tear strength and bending rigidity. The tear strength of textiles is generally deteriorated after coating because the coating glues the fibres together in bundles and reduces the mobility of the fibres/yarns vis-à-vis each other (Bulut and Sülar 2011). It is however highly interesting that coating B instead increased the tear strength of the samples and a possible explanation could be a plasticizing effect of coating B, i.e.…”
Section: Textile Properties and Durabilitymentioning
confidence: 87%
“…Some textile testing standards relevant for the application in this study were chosen: For coated textiles, it is particularly interesting to study the change in tear strength with the coating since this is the property that is most likely to differ (Bulut and Sülar 2011). The abrasion resistance can tell something of how well the coating remains on the textile during wear, but is not demanding enough to truly challenge most coatings.…”
Section: Introductionmentioning
confidence: 99%